Quetiapine extended‐release vs olanzapine for Japanese patients with bipolar depression: A Bayesian analysis - Taro Kishi; Toshikazu Ikuta; Yuki Matsuda; Nakao Iwata (Wiley, 2019)
Abstract Objective It is unknown whether there are differences in efficacy and safety between quetiapine extended‐release, 300 mg/d (QUEXR300), and olanzapine, 5‐20 mg/d (OLA), for Japanese patients with bipolar depression. Methods We conducted a Bayesian analysis of data from phase 3 studies in Japan of QUEXR300 and OLA. Outcomes were remission rate (primary), response rate, improvement on the Montgomery‐Åsberg Depression Rating Scale and 17‐item Hamilton Depression Rating Scale scores, discontinuation rate, and incidence of individual adverse events. We calculated the standardized mean difference (SMD) and the risk ratio (RR) and 95% credible interval (95% CrI) for continuous and dichotomous data, respectively. Results There were no significant differences between QUEXR300 and OLA for any of the efficacy outcomes. QUEXR300 was associated with a higher incidence of somnolence than OLA (RR = 5.517; 95% CrI = 1.563, 19.787), while OLA was associated with greater increase body weight (SMD = −0.488; 95% CrI = −0.881, −0.089) and blood prolactin levels (SMD = −0.642; 95% CrI = −1.073, −0.213) than QUEXR300, and a greater decrease in high‐density lipoprotein cholesterol levels (SMD = −0.408; 95% CrI = −0.785, −0.030) than QUEXR300. Conclusion Although the two drugs' efficacy did not differ, OLA increased the risk of metabolic syndrome and QUEXR300 the risk of somnolence. A large scale, long‐term, head‐to‐head comparison study of QUEXR300 vs OLA for Japanese patients with bipolar depression is needed to confirm the results of the current study.